The fashion factory : design, create and sew your own unique clothes - Riley, Amanda (Quadrille Publishing, 2015)
This is a new kind of making book for today's highly fashion-aware girls and young women. To create the clothes seen within the pages of this book, you don't need any special skills other than an interest in fashion and style, a willingness to have a go and cut up old clothes plus a love of rummaging around in thrift shops. As well as teaching you the basic set of sewing skills as you create garments such as The vintage scarf top and The dungaree dress, this book will aid you to develop an eye for trends, styles, silhouettes, colours and prints.